Semantic And Idiomatic Features Of Interpreting Phraseological Units From English Into Uzbek - et. al., Abidova Rokhatoy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The issue focused on the linguistic distinctiveness of Phraseological units, their grouping, the difficulties in the interpretation of phraseological units, techniques of their interpretation from one language into another.